Personality Changes among Students in a Conservative Seminary - Nauss, Allen (Journal for the scientific study of religion, 1972)
The personality of seminarians in three successive class groups was measured with three inventories near the beginning and end of their training program. Significant changes across class groups were related to five institutional objectives dealing with emotional stability, vocational maturity, desire for the parish ministry, concern for people, and commitment to a specific theological position. Conclusions include: 1) personality change is measurable at the seminary level; 2) the changes can be associated with institutional objectives; 3) nonpersisters are different from persisters; 4) similar patterns of change occurred over the seven-year period; and 5) the personality portrait of a seminarian includes characteristics specific to an individual seminary.